ON THE EMERGENCE OF PSYCHOLINGUISTICS, ITS CURRENT SIGNIFICANCE AND BENEFITS FOR FUTURE GENERATIONS - Abdullayev Shokhzod (Research Focus International Scientific Journal, 2022)
The object and subject of psycholinguistics. Specific features of psycholinguistics: the human factor, the situational factor, the principle of experiment. Conceptual-terminological apparatus. Psycholinguistics as a psychological science. Psycholinguistics and Linguistics. Individuality and communication. The Interrelationship of Psycholinguistics with Other Disciplines.